Frontal Contribution to Hippocampal Hyperactivity During Memory Encoding in Aging - Nyberg, Lars; Andersson, Micael; Lundquist, Anders; Salami, Alireza; Wåhlin, Anders (Frontiers in Molecular Neuroscience, 2019)
Hippocampal hypo- as well as hyper-activation have been reported during memory encoding in older individuals. Prefrontal cortex provides top-down state signals to the hippocampus that bias its computation during memory encoding and retrieval, and disturbed top-down signals could contribute to hippocampal hyper-activation. Here we used > 500 cross-sectional and longitudinal observations from a face-name encoding-retrieval fMRI task to examine hippocampal hypo- and hyper-activation in aging. Age-related anterior hippocampal hypo-activation was observed during memory encoding. Next, older individuals who longitudinally dropped-out were compared with those who remained in the study. Older dropouts had lower memory performance and higher dementia risk, and hyper-activated right anterior and posterior hippocampus during memory encoding. During encoding, the dropouts also activated right prefrontal regions that instead were active during retrieval in younger and older remainers. Moreover, the dropouts showed altered frontal-hippocampal functional connectivity, notably elevated right prefrontal cortex to anterior hippocampus connectivity during encoding. In the context of a general pattern of age-related anterior hippocampal hypo-activation during encoding, these findings support a top-down contribution to paradoxically high anterior hippocampal activity in older dropouts who were at elevated risk of pathology.